ANALISIS MODEL PROJECT BASED LEARNING BERBANTUAN LIVEWORKSHEETS DALAM MENINGKATKAN PRESTASI BELAJAR DAN KETERAMPILAN LITERASI SAINS - Nabil Aulia Prakoso; Rusnilawati Rusnilawati (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2024)
This study aims to analyze the effectiveness of the Project Based Learning (PjBL) model supported by LiveWorksheets in improving learning achievement and science literacy skills of fourth-grade students at SD Muhammadiyah 16 Karangasem. A descriptive qualitative approach was employed using data collection techniques including observation, interviews, and documentation. The research subjects were students from classes IV A and IV B, with the object of the study being the effectiveness of student learning. The results of the study indicate that the effectiveness of student learning can be categorized as moderate, with listening activities obtaining the highest scores and oral activities obtaining the lowest scores. Teachers play a crucial role in enhancing student learning achievement by considering factors such as varied teaching methods, personalized approaches, motivation, and student engagement.The implications of this research provide a deeper understanding of the factors influencing student learning effectiveness, as well as designing more effective teaching strategies.